Carreteras que irradian de Madrid
Contiene planos de: Las Palmas de Grna Canaria, Santander, Vigo, Pontevedra, Segovia, Las Palmas, San Sebastián, Badajoz, Palma de Mallorca, León, Coruña, Granada, Avila, Valencia, Salamanca, Pamplona, Lerida y Huesca